THE FACTORS ANALYSIS THAT INFLUENCE ONINFLATIONIN INDONESIA - Helmi Agus Salim; Nely Supeni (STIE Mandala Jember, 2020)
MBA –JournalofManagementandBusinessAplicationPage 302MBAJournalofManagementandBusinessAplicationTHE FACTORS ANALYSIS THAT INFLUENCE ONINFLATIONIN INDONESIAHelmi Agus Salim1Nely Supeni2Higher Education of Economic MandalaEmail: helmi@stie-mandala.ac.idABSTRACTInflation is an interesting topic to discuss because it has a broad impact on macroeconomic aggregates such as on economic growth, product competitiveness, interest rates and income distribution. Inflation is a dilemma that haunts the economy, especially developing countries especially Indonesia is a country with an estimated economic level in the world. Therefore there are several things that will be studied and examined to find out these problems including the effect of fuel subsidies, the effect of the Rupiah exchange rate against the US Dollar, the influence of interest rates, and the influence of Gross Domestic Product (GDP) on the inflation rate in Indonesia. The research method for analyzing data used is multiple regression. The results showed the Subsidy Variable (LS) had a positive regression coefficient of 0.1270 to inflation, the exchange rate coefficient (LK) was 0.5915 to inflation, the value of the interest rate coefficient (LSB) was -0.88638 to inflation, the GDP coefficient (LG) is 0.1489 of inflation. Based on the simultaneous test, it can be seen that the F statistic is 390 with a prob (F-statistic) of less than one percent, so these statistics mean that together the independent variables in the research model include the value of government subsidies, the exchange rate of the Rupiah against the USD, interest rates, and Gross Domestic Product / GDP of Indonesia together influence the inflation rate in Indonesia.Keywords:Inflation, Rupiah Exchange Rate, Interest Rates, Gross Domestic Product